Listening to cougar - Bekoff, Marc; Lowe, Cara Blessley (University Press of Colorado, 2007)
This spellbinding tribute to "Puma concolor" honors the big cat's presence on the land and in our psyches. Essays describe chance meetings with cougars. Biologists describe aspects of cougar ecology. Conservationists relate the political history of America's greatest cat. Short stories and essays consider cougar's significance to people. A timely and thoughtful blend of natural history and evocation of a mysterious creature.